Islamophobia and Terrorism in Indonesia: an Approach on Neuroscience - Nurkhalis, Nurkhalis (LPPM IAIN Kudus, 2022)
The stigmatization of Islam with Islamophobia in Indonesia leads to a formless war that makes jihad struggles under the Qur’an and Hadith with a “sacred canopy theory” approach. The interpretation of the words shahid, jihad, and qital turned into a holy warrior who was then suggested as terrorists. This research is based on a literature study approach using library research. This study explains the doctrine of terrorism on hatred of infidels, Westerns, freedom, and mini clothes. This makes terrorism perspectives in terms of hatred change neuroscience from the nervous system to an emotion that culminates in an increase in psychopathy so that increasing dendritic polymorphisms make it easier for synapses to choose the path of tragedy. The growth of Islamophobia (fear of Islam) is a result of tahrif (deviating the meaning of a word) from outsiders’ understanding, including terrorists who alter the core truth of Islam. This diversion of meaning is a way to ease the reacting and maneuvering emotions into brutal and sadistic actions. They prioritized their interpretation of dyspraxia (carelessness), incoordination (loss of control), dysphasia (loss of polite communication skills), and hemianopia (blindness). Unstable neuroscience strongly pushes into false consideration or bad faith in choosing to be a militant Muslim.